Effect of internal axial loads on the stability of sway-permitted prismatic columns. (June 2017) - Tian, Weifeng; Zhou, Xuhong; Fan, Chunlei
Abstract: The stability of prismatic columns subjected to internal axial loads is a common issue during engineering analysis and design. Because of the big difference between the effects of internal loads and end loads, the traditional effective length method is not applicable. Current codes do not provide design method for this issue and engineers require the ability to analysis and design this kind of columns efficiently. Using the concept of negative stiffness, a relationship between end loads and internal axial loads applied on sway-permitted prismatic columns is established so that the internal loads can be considered equivalent to end loads and the critical value can be obtained easily by Euler formula. A practical method to determine the second-order effect is also developed. Eigenvalue buckling and elastic nonlinear analyses are performed to examine the proposed method and the comparison results indicate it has high accuracy. Highlights: Negative stiffness of internal axial loads is determined. A relationship between end loads and internal axial loads is established. Method to determine the critical value of internal axial loads is developed. Method to determine the second-order effect is developed.